A comprehensive multi-level approach for passing Safe Routes to School and Complete Streets policies in Hawaii - Heinrich, Katie M.; Aki, Nancee N.; Hansen-Smith, Heidi; Fenton, Mark; Maddock, Jay (My University, 2012)
Background: Policy changes were needed to reshape the built environment for active transportation. Methods: Using the social ecological model as a framework, the Healthy Hawaii Initiative worked with a contractor to develop a series of meetings, planning sessions, and workshops. Activities spanned 22 months between 2007 and 2009, and involved multiple stakeholders, including educational outreach for legislators and collaborative planning sessions with advocates. Results: Ultimately, with the help of the contractor to initiate the process, Complete Streets and Safe Routes to School (SRTS) legislation were introduced January 2009. Advocacy groups monitored bill progress, testified at hearings, and assisted in rewording the bills. The SRTS statute required the Department of Transportation (DOT) to administer the federal SRTS funds and the complete streets law tasked the state and county DOTs to adopt complete streets policies and review existing highway design standards and guidelines. Both bills were signed into law June 2009. Conclusions: Focusing efforts at multiple levels of the social ecological model involving champions and key stakeholders led to the successful passage of legislation supporting active transportation. Tracking policy implementation and evaluation over time will help determine actual impact on active transportation behaviors across Hawaii.
Keywords: Social-ecological model; Elected officials; Physical activity; Legislation